(untitled) (Revista Română de Jurnalism și Comunicare, 2025)
This study explores how the structural characteristics and historical development of journalism education in Hungary shape perceptions and practices related to Mobile Journalism (MoJo) within the field of Communication and Media Studies (CMS). Drawing on two empirical investigations – a national stakeholder survey conducted as part of a cross-country research project on MoJo in Central and Eastern Europe, and a content analysis of Hungarian CMS curricula – the paper examines the integration of MoJo in higher education and professional training. Findings reveal that while students generally view MoJo as a legitimate form of journalism, formal education in this field remains limited. The majority of students acquire relevant skills through informal learning, and there is little institutional commitment to teaching MoJo due to structural constraints and a declining interest in journalism as a career path. CMS curricula rarely include MoJo-related content, and where journalism is present, it is often embedded as a secondary component. Based on these findings, the paper recommends updating existing journalism-related courses and strengthening cooperation with media professionals to enhance MoJo training. Overall, the paper provides insights into the broader educational context influencing journalism innovation in Hungary and offers practical recommendations for aligning journalism education with digital trends.